Influence of container-type and positioning on growth of tomato plants and suppression of meloidogyne javanica exposed to biomuti and afrikelp - Sebati, Mmagadima Lauraine (My University, 2019)
The influence of cultural practices can be modified by environmental conditions such as container-type or positioning. The objective of the study was to determine whether container-type and positioning would have an influence on the growth of tomato plants and suppression of Meloidogyne javanica exposed to biomuti (Trial 1) and Afrikelp (Trial 2). Different container-types were filled with approximately 10.4 L growing mixture comprising steam-pasteurised sandy loam soil and Hygromix-T at 3:1 (v/v) ratio. The containers were established in microplots at 0.6 m × 0.6 m spacing, with treatments being brown pot-below; brown pot-above, black pot-below, black pot-above, plastic bag-above and plastic bag-below. Tomato (Solanum lycopersicum L.) cv. 'Floradade' seedlings were each transplanted and irrigated with 500 ml chlorine-free tapwater every other day. Seven days after transplanting, each plant was inoculated with 2000 eggs and second-stage juveniles (J2) of M. javanica. Biomuti and Afrikelp, obtained from the Agricultural Research Council (ARC) Vegetable, Ornamentals and Plants (VOP), were applied in separate trials weekly at 2.5%. At 56 days after inoculation, plant growth including selected nutrient elements and nematode variables were measured. Data were subjected to analysis of variance, with separation of means achieved using Fisher’s Least Significant Difference test at the probability level of 5%. In the biomuti trial, container-type and positioning had a significant effect on plant height, fruit number, dry root mass, dry shoot mass and fruit mass, contributing 82, 48, 44, 85 and 89% in total treatment variation (TTV) of the respective variables. Relative to brown pot-below; black pot above, plastic bag-above and brown pot-above reduced plant variables, whereas treatment effects were not significant on nematode variables. In the Afrikelp trial, trends where similar to those in biomuti, treatments had highly significant effects on xvi plant height, dry root mass, dry shoot mass and gall rating, contributing 91, 88, 66 and 60% in TTV of the respective variables. Relative to brown pot-below; black pot above, plastic bag-above and brown pot-above reduced the plant variables, but had no significant effects on nematode variables. Generally, plastic bags and polyethylene pots below-ground improved most plant growth variables when compared to those in containers positioned above-ground.
Thesis (M. A. Agriculture (Plant Protection)) -- University of Limpopo, 2019
Keywords: Container-type and positioning; Tomato plants; Meloidogyne javanica; Container gardening; Tomatoes -- Breeding; Plants, Potted; Javanese root-knot nematode